Lestaurtinib inhibits Citron kinase activity and medulloblastoma growth through induction of DNA damage, apoptosis and cytokinesis failure - Pallavicini, Gianmarco; Iegiani, Giorgia; Parolisi, Roberta; Ferraro, Alessia; Garello, Francesca; Bitonto, Valeria; Terreno, Enzo; Gai, Marta; Di Cunto, Ferdinando (Frontiers in Oncology, 2023)
Medulloblastoma (MB), the most common malignant pediatric brain tumor, is currently treated with surgery followed by radiation and chemotherapy, which is accompanied by severe side effects, raising the need for innovative therapies. Disruption of the microcephaly-related gene Citron kinase (CITK) impairs the expansion of xenograft models as well as spontaneous MB arising in transgenic mice. Although no specific CITK inhibitors are available, Lestaurtinib, a Staurosporine derivative also known as CEP-701, inhibits CITK with IC50 of 90 nM. We therefore tested the biological effects of this molecule on different MB cell lines, as well as in vivo, injecting the drug in MBs arising in SmoA1 transgenic mice. Similar to CITK knockdown, treatment of MB cells with 100 nM Lestaurtinib reduces phospho-INCENP levels at the midbody and leads to late cytokinesis failure. Moreover, Lestaurtinib impairs cell proliferation through CITK-sensitive mechanisms. These phenotypes are accompanied by accumulation of DNA double strand breaks, cell cycle block and TP53 superfamily activation in vitro and in vivo. Lestaurtinib treatment reduces tumor growth and increases mice survival. Our data indicate that Lestaurtinib produces in MB cells poly-pharmacological effects extending beyond the inhibition of its validated targets, supporting the possibility of repositioning this drug for MB treatment.